Promoting the effects of CuSO4 on N2 selectivity in selective catalytic oxidation of ammonia over Pt/TiO2 catalysts. (21st October 2022) - Yu, Yanke; Geng, Mengqiao; Wei, Desheng; He, Chi
Abstract : The NH3 -SCO reaction mechanism over a Pt/TiO2 catalyst was transferred into the i-SCR mechanism after adding CuSO4, and thus the formation of N2 was promoted. Abstract : Selective catalytic oxidation of NH3 (NH3 -SCO) is a promising method to reduce NH3 pollution. The Pt-based catalysts exhibited excellent activity in the NH3 -SCO reaction under low temperatures. However, it was easy for the NH3 to be oxidized to N2 O and NO x (NO and NO2 ) over the Pt-based catalyst, causing a low N2 selectivity. The CuSO4, which could supply both Brønsted and Lewis acid sites on the catalyst, was used to promote N2 selectivity. The N2 adsorption–desorption, X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), inductively coupled plasma mass spectrometry (ICP-MS), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), NH3 -temperature programmed desorption (NH3 -TPD), H2 -temperature programmed reduction (H2 -TPR) and in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) were used to characterize the catalyst. The addition of CuSO4 could suppress the formation of N2 O and NO x, thus the highest N2 selectivity on the catalyst increased from 21.2% to 78.1%. An imide mechanism was the main reaction mechanism on the Pt/TiO2 catalyst. After adding CuSO4, the NH3 -SCO reaction over the CuSO4 -Pt/TiO2 catalyst mainly followed an i-SCR mechanism where NH3 was oxidized to N2 O and NO x, and then the newly formed N2 O and NO x were reacted with NH3 /NH4 + adsorbed on the Lewis and Brønsted acid sites via an NH3 -SCR reaction over the catalyst, and finally N2 was formed. The acid sites performed an important role in the formation of N2 and this work should provide an effective method to promote N2 selectivity in a NH3 -SCO reaction.